Community participation in natural resources management: A case of natural forest management in Manyoni district - Augustino, Kidenya Eliutha (2023)
Dissertation submitted to the Institute of Development Studies in Partial Fulfillment of the Requirements for the Award of Master of Science in Development Policy (MSc DP) of Mzumbe University